Insulin Resistance Predicts Postoperative Cognitive Dysfunction in Elderly Gastrointestinal Patients - He, Xi; Long, Ge; Quan, Chengxuan; Zhang, Bin; Chen, Jia; Ouyang, Wen (Frontiers in Aging Neuroscience, 2019)
BACKGROUND: Aging population undergoing surgery are at risk of postoperative cognitive dysfunction (POCD). Exploring effective and reliable early predictor of POCD is essential to identify high-risk patients and make prospective decisions. The purpose of this study was to examine whether preoperative insulin resistance, is an independent predictor of POCD. METHODS: A total of 124 aged 60 years older patients for gastrointestinal surgery were enrolled in a prospective observational clinical study. All participants completed a battery of neuropsychological tests before surgery and at 7 days afterwards. POCD was defined as a decline of at least 1.5 SD on two or more of neuropsychological tests. Plasma concentration of tumor necrosis factor α (TNF-α), C-reactive protein (CRP), and S-100β protein were measured. The status of insulin resistance was assessed by Homeostasis Model Assessment–Insulin Resistance (HOMA-IR). The relationship between HOMA-IR and POCD was assessed by Multivariable logistic regression models and the receiver operating characteristic curve. RESULTS: 51 patients (41.1%) were diagnosed with POCD at 7 days after surgery. Preoperative HOMA-IR values of the POCD group were significantly higher than the non-POCD group, besides, CRP and TNF-α levels of the POCD group were significantly higher at each postoperative time point (P<0.05). Preoperative HOMA-IR value was an independent predictor of POCD (adjusted OR 1.88, 95% CI 1.18-2.99) even after adjust for confounding variables, and when dichotomized, individuals above the HOMA-IR threshold (HOMA-IR >2.6) had a three time’s higher risk of POCD (OR 3.26; 95% CI 1.07–9.91) compared individuals below the threshold. The areas under the receiver operating characteristic curve of HOMA-IR was 0.804 (95% CI, 0.725–0.883; P <0 .001).The optimal cutoff value was found to be 0.583, with sensitivity of 84.3% and specificity of 74%. HOMA-IR value was positively associated with TNF-α concentration at baseline (R2= 0.43, P < 0.01) and 1 days after surgery (R2= 0.3861, P < 0.01). CONCLUSIONS: Preoperative insulin resistance is an effective predictor for the occurrence of POCD. Targeted prevention and treatment strategies of insulin resistance may be effective interventions of patients at risk for POCD.